Ultrasound-assisted extraction of resveratrol from functional foods: Cookies and jams - Palma, M. (2016)
Rapid extraction techniques with ultrasonic systems have been established to extract resveratrol from two functional foods, namely cookies and jams. The ultrasound-assisted extraction (UAE) was optimized using a full factorial design with three variables: solvent composition (10-70% and 30-90% methanol in water for cookies and jams, respectively), solvent-to-solid ratio (10:1-40:1), and ultrasonic probe diameter (2 and 7. mm). The extraction kinetics (5-30. min) were studied to confirm the full recovery of resveratrol from the functional foods. The resveratrol was quantified by Ultrahigh Performance Liquid Chromatography with a Fluorescense Detector (UPLC-FD).The solvent composition was found to have a significant effect on the recovery (p <. 0.005) for both of the functional foods studied. The optimal UAE conditions were 90% methanol in water, an extraction time of 10. min, an ultrasonic probe with a diameter of 7. mm, and solvent-to-solid ratios of 40:1 and 10:1, respectively, for cookies and jams.The methods developed in this study show a high precision in terms of Coefficient of Variance (CV), with values of less than 5% for both repeatability and intermediate precision. The applicability of the methods to real samples has been evaluated and it was confirmed that the methods are suitable for the extraction of resveratrol from cookies and jams. © 2015 Elsevier Ltd.